Dealing with under-preparedness in engineering education. Part 1: Defining the goal. A taxonomy of engineering competency. - Woollacott, L.C. (My University, 2008)
This paper emerges from work conducted on the problem of effectively addressing under-preparedness in entrants to university engineering programs in South Africa. Any educational curriculum is based on a conception of the developmental journey a learner must take in becoming a competent graduate. The conceptions underlying traditional engineering curricula do not match well with the journeys that under-prepared students with ability should take to reach their potential fully. To work towards a better match between conception and reality requires deeper understanding of the nature of under-preparedness, of engineering competency and of the determinants of engineering competency (that is, the underlying factors that determine the quality of the competencies). The first of these areas will inform the process of curriculum design by clarifying the starting point of the developmental journey. The second area will clarify the goal and the third will help to clarify what must be done to get there. This paper addresses the second of these issues –understanding engineering competency. Eight different perspectives on engineering competency have been extracted from the literature and a ninth is developed in the paper. Analysis of their similarities and differences provides a basis for developing a broader, integrated perspective that is presented as a taxonomy of engineering competency. How the taxonomy is used in acquiring a deeper understanding of competency determinants and under-preparedness will be explored in two follow up papers.
Proceedings of the 2003 WFEO/ASEE e-Conference, American Society for Engineering Education.
Keywords: Engineering Education; Accreditation; Engineering competency; Graduate attributes; Under-preparedness